Fabrication and Characterization of Directional Couplers as Power Dividers - Andriawan, Alan; Rahayu, Lucky Putri; Pramono, Yono Hadi (IPTEK Journal of Proceedings Series, 2019)
This paper is about directional coupler fabrication results in a slab structure with a substrate in the form of acrylic glass, a film of nano SnO2, and cladding in the form of methyl methacrylate (MMA). The length of the interaction area (Lc) directional coupler of the fabrication result is 5 mm with a gap width (g) of 0.353 mm. SnO2 film is grown by deposition on an acrylic substrate. To facilitate the characterization process, the directional coupler is given an optical fiber as input. SnO2 film which has been deposited on an acrylic substrate is coated with methyl methacrylate (MMA). Coating of methyl methacrylate (MMA) in SnO2 film is done by the doctor blade method. Directional coupler fabrication results are used as optical power dividers. The fabricated directional coupler is narrated using a He-Ne laser with a wavelength of 632.8 nm. The characterization mechanism is carried out by taking a photo of the cross section of the directional coupler when given a laser beam input. The cross section photos are processed using ImageJ software to determine the directional coupler intensity distribution on each port. Based on the results of the characterization, the directional coupler with the 5 mm Lc output percentage is 26%, 24%, and 49%